Effect of Different Cu Levels on Growth of Earthworm, Eisenia fetida in a Calcareous Soil - Jenabi Haghparast, Raheleh; Golchin, Ahmad; Kahneh, Ehsan (Asian Journal of Chemistry, 2013)
Destructive effects of heavy metals on the environment and the microorganisms have been reported. Heavy metals such as Cu break through different ways into agricultural land and the environment. In order to study effects of soil contamination concentrations, 0, 10, 20, 40, 60, 80 mg Cu concentration per kg soil have been tested on the growth of earthworm species Eisenia fetida. The results showed that average concentrations of Cu up to 60 mg/kg soil increased and stimulated earthworm growth parameters. But higher concentrations 80 mg/kg soil have significant negative effects on the mean weight, survivability and number of Cocoon produced. Amount of Cu in earthworm organs was a linear function of the Cu concentration in its living environment.